Enrichment of infection-associated bacteria in the low biomass brain bacteriota of Alzheimer's disease patients. - Yeon Kyeong Ko; Eunbi Kim; Eun-Jae Lee; Soo Jeong Nam; Yeshin Kim; Seongheon Kim; Se-Young Choi; Hyun Young Kim; Youngnim Choi (PLoS ONE, 2024)
Alzheimer's disease (AD) is a neurodegenerative disease accompanied by neuroimmune inflammation in the frontal cortex and hippocampus. Recently, the presence of bacteria in AD-affected brains has been documented, prompting speculation about their potential role in AD-associated neuroinflammation. However, the characterization of bacteriota in human brains affected by AD remains inconclusive. This study aimed to investigate potential associations between specific bacteria and AD pathology by examining brain tissues from AD-associated neurodegenerative regions (frontal cortex and hippocampus) and the non-AD-associated hypothalamus. Employing 16S rRNA gene sequencing, 30 postmortem brain tissue samples from four individuals with normal brain histology (N) and four AD patients were analyzed, along with three blank controls. A remarkably low biomass characterized the brain bacteriota, with their overall structures delineated primarily by brain regions rather than the presence of AD. While most analyzed parameters exhibited no significant distinction in the brain bacteriota between the N and AD groups, the unique detection of Cloacibacterium normanense in the AD-associated neurodegenerative regions stood out. Additionally, infection-associated bacteria, as opposed to periodontal pathogens, were notably enriched in AD brains. This study's findings provide valuable insights into potential link between bacterial infection and neuroinflammation in AD.